Health-related impediments to learning among dental and oral surgery students. Issue 1 (2nd January 2019) - Kernan, William D.
Abstract: Dental education is a challenging experience that places significant demands on students' intellectual, financial, and psychosocial well-being. Dental students who simultaneously experience physical illness, emotional upset, or interpersonal difficulty may be at greater risk of experiencing negative academic consequences. It is well documented that stress affects student learning, however, the impact of other health concerns on academic success is less understood. The purpose of this manuscript is to document the prevalence and perceived academic impact of 24 health concerns on the academic performance of a sample of 130 undergraduate dental students as measured by the National College Health Assessment (NCHA). Health concerns that were most prevalent among dental students were generally also perceived to be most detrimental to their learning. These included upper respiratory infections (cold, flu, sore throat), interpersonal concerns (concerns about a troubled friend or family member, and relationship difficulty), and mental health issues (depression/anxiety/seasonal affective disorder, and stress).